2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7471645
|View full text |Cite
|
Sign up to set email alerts
|

A distributed algorithm for robust LCMV beamforming

Abstract: In this paper we propose a distributed reformulation of the linearly constrained minimum variance (LCMV) beamformer for use in acoustic wireless sensor networks. The proposed distributed minimum variance (DMV) algorithm, for which we demonstrate implementations for both cyclic and acyclic networks, allows the optimal beamformer output to be computed at each node without the need for sharing raw data within the network. By exploiting the low rank structure of estimated covariance matrices in time-varying noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…(4) in a fully distributed manner? We will first show that (4) can be transformed to a NSGC problem by utilising a tight convex relaxation, as previously demonstrated in [16]. To do so, we introduce local variables y i,k and impose the constraint that, at consensus…”
Section: Iii-a Example: Constrained Quadratic Programmingmentioning
confidence: 98%
See 1 more Smart Citation
“…(4) in a fully distributed manner? We will first show that (4) can be transformed to a NSGC problem by utilising a tight convex relaxation, as previously demonstrated in [16]. To do so, we introduce local variables y i,k and impose the constraint that, at consensus…”
Section: Iii-a Example: Constrained Quadratic Programmingmentioning
confidence: 98%
“…it can be shown that problems (5) and (3) are equivalent [16]. As the stationary points of (6) occur when…”
Section: Iii-a Example: Constrained Quadratic Programmingmentioning
confidence: 99%
“…In contrast, in [16], an optimal distributed beamformer was proposed for use in cyclic networks by exploiting the structure of estimated CPSDMs to cast LCMP beamforming as distributed consensus. However, for CPSDM estimates based on a large number of frames, the proposed algorithm's communication cost scaled poorly.…”
Section: Distributed Linearly Constrained Beamformersmentioning
confidence: 99%
“…In a similar vein, in [26], a distributed beamformer based on the pseudo-coherence principle was proposed. Similar to [16], the method in [26] can operate in cyclic networks. Furthermore, the authors demonstrated how the algorithm could perform near optimally with only a finite number of iterations, resulting in low transmission complexity.…”
Section: Introductionmentioning
confidence: 99%
“…We construct our distributed optimization problem in a similar manner to the approach in [29]. First thing to notice is that the enhanced signal would not be accessible in a distributed manner unless the locally calculable output, Z m , becomes a side product of the algorithm or an optimization parameter itself.…”
Section: Distributed Optimization With Pdmmmentioning
confidence: 99%